Information supply of population concerning self-medication: state, problems and ways of optimization - I. V. Nizhenkovskaya; A. Yu. Lysenko; I. N. Dikukha (Zaporožskij Medicinskij Žurnal)
In the article the results of the study of self-medication process prevalence among Kiev inhabitants are presented. The research was conducted via a questionnaire. The main factors which have an influence on the development of this practice were defined as well as the sources of information about remedies for self-medication which are the most asked by inhabitants.